Feasibility study of a menstrual health behaviour change intervention for women and girls with intellectual disabilities and their caregivers for Vanuatu's humanitarian responses. - Jane Wilbur; Casey-Lynn Crow; Relvie Poilapa; Chloe Morrison (Public Library of Science (PLoS), 2024)
The Veivanua campaign is a menstrual health intervention for people with intellectual disabilities and their caregivers in Vanuatu's humanitarian setting. The campaign was adapted from the Bishesta campaign delivered in Nepal's development setting. This feasibility study is designed to assess the feasibility and acceptability of the Veivanua campaign to understand if efficacy testing is warranted. The Veivanua campaign was delivered to a preselected group of 30 young people (individuals with intellectual disabilities) and 35 caregivers (males and females). Data were collected through several qualitative tools to allow for methods triangulation: process monitoring, post-intervention in-depth interviews with caregivers and nine young people, observation of young persons, photovoice and ranking with two young people, campaign resource ranking, and key informant interviews with staff involved in the intervention. Data were analysed thematically using Nvivo 12. Results show that the Veivanua campaign is feasible. Male and female caregivers reported an increased ability to support young people's menstrual health and greater preparedness for the next emergency. Young people understood the training and applied their learning. Key informants want to scale up the intervention in their humanitarian responses. Several changes were made to the adapted campaign, but similar outcomes were recorded in Nepal and Vanuatu. All target behaviours improved, and campaign resources were used, but many caregivers found the menstrual calendar confusing. The intervention was not delivered with fidelity but responded to the context. The campaign cost more than the Bishesta campaign because procurement was more expensive in Vanuatu. In conclusion, this is the first intervention globally, so it begins to fill a substantial gap, but more must be done. As the Veivanua campaign is feasible, it requires efficacy testing in Vanuatu. It should also be adapted to humanitarian crises in other countries to support the menstrual health of this previously excluded population.